Assessment of Pelvic Organ Prolapse by Pelvic Organ Prolapse Quantification Technique Among Pre-operative Patients - Pradhan, T; Regmi, MC; Rai, R; Bhatta, R; Rijal, P; Uprety, DK (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: This was performed to examine pelvic organ prolapse using POP-Q technique and correlate pre-existing urinary symptoms with segments of pelvic organ prolapse. Methods: All patients admitted with pelvic organ prolapse were included. Patients were asked regarding any concomitant urinary symptoms and then all patients were examined by POP-Q technique and correlation of urinary symptoms was done with various segments of pelvic organ prolapse. Results: Eighty patients were studied in one year duration. Majority of patients had presented with stage 4 prolapse (58.8%). Majority of patients had urinary symptoms among which 87.5% had increased urinary frequency, 88.8% had dysuria, 65% had stress urinary incontinence (SUI), 72.5% had incomplete evacuation. Dysuria and SUI was found to have significant correlation with anterior segment prolapse (p<0.05%). Conclusions: Site specific measurements by POP-Q system showed anterior segment prolapse to be more and were significantly associated with various urinary symptoms. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 2 / Issue 16 / July-Dec, 2013 / 26-29 DOI: http://dx.doi.org/10.3126/njog.v8i2.9765